(untitled) (LEGAL DIALOGICA, 2025)
This research examines the legal basis of the application of chemical castration penalties against perpetrators of sexual crimes against children, as well as factors that affect the implementation of chemical castration sanctions in preventing sexual crimes against children. The method used is normative legal research to analyze existing regulations and the effectiveness of these criminal acts. The research results show that the application of chemical castration is based on the state’s commitment to protect children from extraordinary threats of sexual crimes. Prevention should prioritize educational, preventive, and rehabilitative approaches, not just extreme sanctions. This study recommends the need for public education regarding legal risks and strengthening the capacity of law enforcement officers, as well as a rehabilitation approach as an alternative to prevent sexual crimes against children. Abstrak: Penelitian ini mengkaji dasar hukum penerapan pidana kebiri kimia terhadap pelaku kejahatan seksual terhadap anak, serta faktor yang mempengaruhi pelaksanaan sanksi Kebiri Kimia dalam mencegah kejahatan seksual terhadap anak. Metode yang digunakan adalah penelitian hukum normatif untuk menganalisis regulasi yang ada dan efektivitas tindakan pidana tersebut. Hasil penelitian menunjukkan bahwa penerapan pidana kebiri kimia didasarkan pada komitmen negara untuk melindungi anak dari ancaman kejahatan seksual yang bersifat luar biasa. Pencegahan seharusnya lebih mengedepankan pendekatan edukasi, preventif, dan rehabilitatif, bukan hanya pada sanksi ekstrim. Penelitian ini merekomendasikan perlunya pendidikan masyarakat mengenai risiko hukum dan penguatan kapasitas aparat penegak hukum, serta pendekatan rehabilitatif sebagai alternatif untuk mencegah kejahatan seksual terhadap anak.